E-Counselling for Learner Support Services in ODL Institutions: A Practical Approach - A. C. Ukwueze (West African Journal of Open and Flexible Learning)
Like in conventional institutions, students in open education encounter various problems ranging from social, psychological, vocational to academic challenges, which impede their performance and retention. Their case is worsened by the virtual nature of their studies, which demands adequate support in order to engage in meaningful learning and studentship. This paper therefore explains e-counselling as an innovative learner support service necessary to engage students in open education. E-counselling is an online counselling that provides students with the platform to interact with their counsellors using a variety of social media networks. Efforts were made to look at some networks that could be made available for e-counselling in open education such as Facebook, e-mail (g-mail, Google talk, Skype, WhatsApp), twitter, video conferencing, blog, instant messaging and chat among others. These social media networks ensure that students are not isolated as they provide better alternative to face-to-face counselling, which many experts now see as narrow, archaic and selective in the face of the present technological advancement of the entire world. Some fundamental challenges facing the use of this innovative platform include power failure, poverty, illiteracy and attitudinal problems towards the use of computers. Ideally, every open education institution should have a robust learner support services unit with adequate facilities necessary for e-counselling in order to engage students in meaningful virtual academic activities.